Developing organizational capabilities to deliver lean and green project outcomes using BIM. Issue 10 (3rd October 2018) - Ahuja, Ritu; Sawhney, Anil; Arif, Mohammed
Abstract : Purpose: The purpose of this paper is to describe the process through which an organization develops organizational capabilities by tapping the technical skills and social skills of its employees in the use of Building Information Modeling (BIM) to deliver lean and green project outcomes. The resulting framework for BIM-based organizational capabilities development comprising of three hierarchical layers – technology, process and outcomes – is explained. Design/methodology/approach: For this study, BIM has been identified as an enabler and a process for achieving lean and green outcomes on construction projects. Based on a detailed literature review, this paper identifies the organizational capabilities needed by the architecture, engineering and construction organizations to effectively implement BIM on construction projects. The study has been conducted through a sequential mixed-method approach involving semi-structured interviews, focus groups and qualitative comparative analyses. Findings: It was discovered that to attain desired project outcomes, an organization needs to embrace an underlying BIM adoption culture not only within its project teams but also within the organization as a whole. The study also concluded that an integrated approach to BIM usage – connecting it with lean and green initiatives – on construction projects resulted in improved project outcomes, especially ones targeting lean and green aspects of improvements. Practical implications: The proposed outline for BIM-based organizational capabilities will help the organizations focus on the "human factors" along with the technical factors while striving for successful usage within their organizations. Originality/value: Using the organizational capabilities matrix, this paper highlights the importance of technical and social skill sets of an individual employee and their role in developing the organizational capabilities to gain the desired lean and green outcomes.